Composite sheet for chip bonding and preparation method thereof
By using copper sheets and silver-containing presintered composite sheets for chip bonding, the problem of insufficient thermal conductivity and electrical conductivity of aluminum bonded wires in the prior art is solved, efficient chip heat dissipation and electrical signal transmission are achieved, and ensuring that The chip is safe.
Patent Information
- Application Number
- CN202411518189.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art, the aluminum bonded wire of the power semiconductor module has low thermal conductivity and electrical conductivity, resulting in poor chip heat dissipation and electrical signal transmission, and traditional copper bonded wires are prone to chip damage during bonding.
The chip bonding is carried out by copper sheet and the silver-containing presintered layer composite sheet to achieve effective heat dissipation and electrical signal transmission through the high thermal conductivity and conductivity of the copper sheet, and the chip is directly sintered through the silver-containing presintered layer to avoid additional operations. , ensure the safety of the chip.
It realizes efficient chip heat dissipation and electrical signal transmission, avoids chip damage, and is simple to operate without additional connection or transition layer.
Smart Images

Figure BDA0005107296450000111 
Figure BDA0005107296450000121 
Figure BDA0005107296450000131
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electronic packaging, and in particular to a composite sheet for chip bonding and a preparation method thereof. Background Art
[0002] In the prior art, power semiconductor modules are mainly wire bonded by setting aluminum bonding wires on the chip. However, since the thermal conductivity and electrical conductivity of aluminum bonding wires are relatively low, it is not conducive to the heat dissipation and electrical signal transmission of the chip after setting. Especially for the new generation of power semiconductors represented by silicon carbide and gallium nitride, this defect will greatly limit the application range of the product. For this reason, people try to use copper bonding wires or copper-silver bonding wires with higher thermal conductivity and electrical conductivity as a substitute. However, the power and pressure required for copper bonding wires during bonding are relatively high, which can easily cause chip damage. The processing difficulty and processing cost of copper-silver bonding wires are relatively high, and in the absence of buffer settings, they can still cause chip damage. Summary of the invention
[0003] Based on the defects of the prior art, the purpose of the present invention is to provide a composite sheet for chip bonding. The product is a composite of a copper sheet and a silver-containing pre-sintered layer set in specific size and composition. The material itself has high thermal conductivity and electrical conductivity. When in use, it is only necessary to realize wire bonding directly on the surface of the copper sheet and connect the chip to the silver-containing pre-sintered layer to complete chip bonding. There is no need to set up additional operations. It is easy to use and ensures that the chip will not be damaged.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is:
[0005] A composite sheet for chip bonding, comprising a copper sheet and a silver-containing pre-sintered layer;
[0006] The thickness ratio of the copper sheet to the silver-containing pre-sintered layer is (1-3):1;
[0007] The thickness of the silver-containing pre-sintered layer is 0.03 to 0.2 mm;
[0008] The silver paste used to form the silver-containing pre-sintered layer includes the following components in parts by weight per 100 parts:
[0009] 1-4 parts of dispersant, 0.5-2 parts of reducing agent, 2-5 parts of binder, 1.5-7 parts of diluent and the balance of silver powder;
[0010] The silver powder includes nano-scale silver powder and micro-scale silver powder, and the mass ratio of the two is (5-12):1;
[0011] The particle size D of the nano silver powder v50 ≥20nm;
[0012] The particle size D of the micron-sized silver powder v50 ≤10μm.
[0013] In order to take into account both the bonding strength during chip bonding and the degree of chip protection, in the scheme described in the present invention, a copper sheet and a silver-containing pre-sintered layer are compounded to form a composite sheet. This product can be directly used for chip bonding. When in use, it only needs to be cut into the required size corresponding to the chip, and directly sintered and connected to the chip through the silver-containing pre-sintered layer, and copper bonding wires are set on the surface of the copper sheet for bonding connection, avoiding the heat dissipation and electrical signal transmission problems caused by the use of traditional aluminum bonding wires, and will not cause direct damage to the chip. This product does not require additional connection layers or transition layers when in use, and is easy to operate.
[0014] However, during the research and development, the inventors discovered that the thickness setting of the copper sheet and the silver-containing pre-sintered layer has a great influence on the effect of the product when used. The silver-containing pre-sintered layer is mainly used for connecting the chip layer and the copper sheet. If the thickness is too thin, the connection between the layers will be loose during sintering, the interlayer bonding strength of the product will be poor, and the protection effect on the chip will be insufficient, causing chip damage; but if the silver-containing pre-sintered layer is too thick, it will easily fall off during processing due to insufficient bonding strength, or stratification will occur during the sintering process, which will also lead to insufficient interlayer bonding strength of the product and poor performance. At the same time, since the dimensional change rates of copper and silver metals at high temperatures are different, the thickness ratio of the two metals also needs to be specially set. If the thickness ratio of the copper sheet to the silver-containing pre-sintered layer is too small, the copper sheet may easily cause local peeling between layers due to bending deformation during the sintering process, resulting in poor interlayer bonding strength of the product, and may even affect the protection of the chip; on the other hand, if the thickness ratio is too large, the copper sheet may have curvature at the edge during the punching process during the product processing, resulting in poor flatness, which will also cause poor interlayer bonding strength of the product.
[0015] In addition, in the silver paste component used to form the silver pre-sintered layer, in order to ensure the sintering effect and dispersibility of the silver powder, it is necessary to introduce two sizes of powders, nanometer and micrometer, for compounding. Micrometer-level silver powder is used as a skeleton to reduce the agglomeration of nanometer-level silver powder and reduce grain defects during initial sintering; and nanometer-level silver powder has adhesive properties, which can effectively bond micrometer-level silver powder and fill the pores between micrometer-level silver powders, thereby improving the density of the overall material and the sintering driving force of the material. However, the size of nanometer-level silver powder cannot be too small, otherwise it will be difficult to disperse and cause agglomeration during the processing, and the expected effect of interlayer connection and chip protection cannot be achieved. The size of micrometer-level silver powder cannot be too large, otherwise the skeleton formed will be too large, the difference in particle size between the two silver powders will be too large, and the bonding effect of nanometer-level silver powder will not be ideal. When matching silver powder, it is necessary to simultaneously introduce a variety of auxiliary agents to ensure the effectiveness of the silver-containing pre-sintered layer: dispersant is used to ensure the dispersibility of silver powder, reducing agent is used to remove the oxide layer at the interface between layers, binder improves the connection strength between the silver-containing pre-sintered layer and the copper sheet, diluent is used to adjust the dispersion viscosity of the overall material during processing. If the ratio between silver powder and the pre-sintered layer is inappropriate, it will also result in poor product performance.
[0016] Preferably, the copper sheet has a thickness of 0.03-0.6 mm.
[0017] More preferably, the copper sheet has a thickness of 0.05 to 0.3 mm.
[0018] For the copper sheet of the composite sheet of the present invention, if it is set thinner, the cost in the processing stage is higher, and its protective effect on the chip is reduced when the copper bonding wire is set. At the same time, too thin will also lead to a decrease in the tightness of the copper sheet and the silver-containing pre-sintered layer during sintering, and the interlayer bonding strength is weakened; and if it is set thicker, the copper sheet processing and punching stage will lead to a decrease in the flatness of the copper sheet, uneven force distribution, and also reduce the interlayer bonding strength. When the thickness of the copper sheet is preferably set within the above range, the product can achieve better interlayer bonding strength.
[0019] Preferably, the thickness of the silver-containing pre-sintered layer is 0.05-0.1 mm.
[0020] When the above preferred thickness setting is selected, the composite sheet prepared by the silver-containing pre-sintered layer can have high interlayer bonding firmness, higher force distribution uniformity and high shear strength while ensuring that the chip is not damaged.
[0021] Preferably, the particle size D of the micron-sized silver powder is v50 2~10μm.
[0022] More preferably, the particle size D of the micron-sized silver powder is v50 4~6μm.
[0023] Preferably, the particle size D of the nano-scale silver powder is v50 It is 20~500nm.
[0024] More preferably, the particle size D of the nano-scale silver powder is v50 It is 30~200nm.
[0025] As mentioned above, the combination of micron-scale silver powder and nano-scale silver powder in a specific proportion can take into account the driving force during sintering of the silver-containing pre-sintered layer and the dispersion uniformity and densification effect of the overall silver powder. When the two silver powders of the above-mentioned particle sizes are preferably used in combination, the shear strength of the sintered layer can be made higher, and the interlayer bonding strength of the product and the degree of protection of the chip can be higher.
[0026] Preferably, the dispersant includes at least one of vinyl pyrrolidone, polydiallyl dimethyl ammonium chloride, and sodium dodecyl sulfate; the reducing agent includes rosin acid; the binder includes α-terpineol; and the diluent includes at least one of ethylene glycol and acetone.
[0027] Preferably, the copper sheet is subjected to a softening annealing treatment, and the temperature during the softening annealing treatment is ≥ 200°C.
[0028] Another object of the present invention is to provide a method for preparing the composite sheet for chip bonding, comprising the following steps:
[0029] (1) After pre-treating the copper strip, performing a softening annealing treatment in a reducing atmosphere, and cutting to obtain a copper sheet; the temperature during the softening annealing is ≥ 200° C.;
[0030] (2) The silver paste used to form the silver pre-sintered layer is prepared into a paste slurry according to the components, and then coated on a copper sheet and vacuum dried to obtain the composite sheet for chip bonding.
[0031] The product of the present invention is simple to prepare and operate, and only requires pre-softening annealing and cutting of the copper sheet, and then setting a silver-containing pre-sintered layer on the copper sheet by coating-drying, so that industrial-scale production can be achieved. At the same time, the copper sheet needs to be post-softened and annealed at at least 200° C. for at least 1 hour, otherwise it is difficult to remove stress from the copper sheet, and it is difficult to completely remove the oxide layer on its surface.
[0032] Preferably, the temperature during the softening annealing is 200-500°C.
[0033] More preferably, the temperature during the softening annealing is 300-400°C.
[0034] Preferably, the softening annealing time is ≥ 1 h.
[0035] More preferably, the softening annealing time is 1 to 3 hours.
[0036] The optimized softening annealing temperature and softening annealing time can achieve the purpose of energy saving and cost reduction while ensuring the removal of stress and surface oxide layer of the copper sheet.
[0037] Preferably, the pretreatment of the copper strip in step (1) includes degreasing treatment and hot air drying treatment in sequence;
[0038] More preferably, the degreasing treatment is achieved by soaking the copper strip in a degreasing agent and ultrasonically treating it, followed by ultrasonic cleaning with deionized water.
[0039] More preferably, the hot air temperature during the hot air drying process is 80-100°C.
[0040] Preferably, the reducing atmosphere in step (1) is a mixture of nitrogen and hydrogen, and the volume concentration of hydrogen in the mixture is 3-6%.
[0041] Preferably, the vacuum degree during vacuum drying in step (2) is ≤200 Pa and the temperature is 80-120°C.
[0042] Another object of the present invention is to provide a method for using the composite sheet for chip bonding, comprising the following steps:
[0043] The silver-containing pre-sintered layer of the composite sheet is sintered directly on the chip, and then copper bonding wires are set on the copper sheet surface on the other side of the composite sheet.
[0044] Preferably, the pressure during sintering is pressureless sintering (no pressure is required), the sintering temperature is 240-260° C., and the holding time during sintering is 40-60 min.
[0045] The composite sheet of the present invention has simple steps for use. It only needs to directly sinter the product to fit the chip, and then set a copper bonding wire at the end of the copper sheet to achieve chip bonding. There is no need to additionally apply silver paste or silver slurry and perform subsequent drying and shaping operations, and the operation is convenient.
[0046] The beneficial effect of the present invention is that the present invention provides a composite sheet for chip bonding. The product is a composite of a copper sheet and a silver-containing pre-sintered layer set in a specific size and composition. The material itself has high thermal conductivity and electrical conductivity. When in use, it only needs to realize wire bonding directly on the surface where the copper sheet is located, and the chip can be connected to the silver-containing pre-sintered layer to complete chip bonding. No additional operations need to be set. It is easy to use and ensures that no chip damage will be caused. DETAILED DESCRIPTION
[0047] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.
[0048] Example 1
[0049] The embodiment of the composite sheet for chip bonding and the preparation method thereof described in the present invention,
[0050] The composite sheet comprises a copper sheet and a silver-containing pre-sintered layer;
[0051] The ratio of the thickness of the copper sheet to the silver-containing pre-sintered layer is 3:1;
[0052] Specifically, the thickness of the silver-containing pre-sintered layer is 0.1 mm; the thickness of the copper sheet is 0.3 mm;
[0053] The method for preparing the composite sheet for chip bonding comprises the following steps:
[0054] (1) The copper blank is rolled into a 20 mm wide copper strip, and the copper strip is first soaked in a mixed aqueous solution of 6% ferric chloride and 13% nitric acid as a degreasing agent and ultrasonically treated to remove surface grease, then ultrasonically washed with deionized water, and finally dried with hot air at 90° C. After the treatment, it is softened and annealed at 400° C. for 3 h in a nitrogen mixed gas containing 5% volume concentration of hydrogen, and cut into copper sheets with a length and width of 3*3 mm;
[0055] (2) The silver paste used to form the silver pre-sintered layer is prepared into a paste slurry according to the components, and then coated on a copper sheet, and dried at 100° C. for 20 min under a vacuum environment of 200 Pa to obtain the composite sheet for chip bonding.
[0056] The silver paste used to form the silver-containing pre-sintered layer includes the following components in parts by weight per 100 parts:
[0057] 1 part of dispersant, 0.5 part of reducing agent, 2 parts of binder, 1.5 parts of diluent and the balance of silver powder; the dispersant is a mixture of polyvinyl pyrrolidone, polydiallyl dimethyl ammonium chloride and sodium dodecyl sulfonate in a mass ratio of 2:1:2; the reducing agent is rosin acid; the binder is α-terpineol; the diluent is a mixture of ethylene glycol and acetone in a mass ratio of 2:1;
[0058] The silver powder includes nano-scale silver powder and micro-scale silver powder, and the mass ratio of the two is 12:1;
[0059] The particle size D of the nano silver powder v50 The particle size D of the micron-sized silver powder is 30nm. v50 is 2μm.
[0060] Example 2
[0061] The embodiment of the composite sheet for chip bonding and the preparation method thereof of the present invention is different from the embodiment 1 only in that the ratio of the thickness of the copper sheet to the silver-containing pre-sintered layer is 2:1;
[0062] Specifically, the thickness of the silver-containing pre-sintered layer is 0.1 mm; the thickness of the copper sheet is 0.2 mm.
[0063] Example 3
[0064] The embodiment of the composite sheet for chip bonding and the preparation method thereof of the present invention is different from the embodiment 1 only in that the ratio of the thickness of the copper sheet to the silver-containing pre-sintered layer is 1:1;
[0065] Specifically, the thickness of the silver-containing pre-sintered layer is 0.1 mm; the thickness of the copper sheet is 0.1 mm.
[0066] Example 4
[0067] The embodiment of the composite sheet for chip bonding and the preparation method thereof of the present invention is different from the embodiment 1 only in that the ratio of the thickness of the copper sheet to the silver-containing pre-sintered layer is 1:1;
[0068] Specifically, the thickness of the silver-containing pre-sintered layer is 0.05 mm; the thickness of the copper sheet is 0.05 mm.
[0069] Example 5
[0070] The embodiment of the composite sheet for chip bonding and the preparation method thereof of the present invention is different from the embodiment 1 only in that the ratio of the thickness of the copper sheet to the silver-containing pre-sintered layer is 1:1;
[0071] Specifically, the thickness of the silver-containing pre-sintered layer is 0.03 mm; the thickness of the copper sheet is 0.03 mm.
[0072] Example 6
[0073] The embodiment of the composite sheet for chip bonding and the preparation method thereof of the present invention is different from the embodiment 1 only in that the ratio of the thickness of the copper sheet to the silver-containing pre-sintered layer is 3:1;
[0074] Specifically, the thickness of the silver-containing pre-sintered layer is 0.2 mm; the thickness of the copper sheet is 0.6 mm.
[0075] Example 7
[0076] The embodiment of a composite sheet for chip bonding and a preparation method thereof described in the present invention is different from Embodiment 1 only in that the silver powder includes nano-scale silver powder and micron-scale silver powder, and the mass ratio of the two is 8:1.
[0077] Example 8
[0078] The embodiment of a composite sheet for chip bonding and a preparation method thereof described in the present invention is different from Embodiment 1 only in that the silver powder includes nano-scale silver powder and micron-scale silver powder, and the mass ratio of the two is 5:1.
[0079] Example 9
[0080] The embodiment of the composite sheet for chip bonding and the preparation method thereof of the present invention is different from the embodiment 1 only in that the particle size D of the nano-scale silver powder is v50 is 200nm.
[0081] Example 10
[0082] The embodiment of the composite sheet for chip bonding and the preparation method thereof of the present invention is different from the embodiment 1 only in that the particle size D of the nano-scale silver powder is v50 is 500nm.
[0083] Embodiment 11
[0084] The embodiment of the composite sheet for chip bonding and the preparation method thereof of the present invention is different from the embodiment 1 only in that the particle size D of the nano-scale silver powder is v50 is 20nm.
[0085] Example 12
[0086] The embodiment of the composite sheet for chip bonding and the preparation method thereof of the present invention is different from the embodiment 1 only in that the particle size D of the micron-sized silver powder is v50 is 4μm.
[0087] Example 13
[0088] The embodiment of the composite sheet for chip bonding and the preparation method thereof of the present invention is different from the embodiment 1 only in that the particle size D of the micron-sized silver powder is v50 is 6μm.
[0089] Embodiment 14
[0090] The embodiment of the composite sheet for chip bonding and the preparation method thereof of the present invention is different from the embodiment 1 only in that the particle size D of the micron-sized silver powder is v50 is 10μm.
[0091] Embodiment 15
[0092] The embodiment of the composite sheet for chip bonding and the preparation method thereof of the present invention is different from the embodiment 1 only in that the particle size D of the nano-scale silver powder is v50 is 500nm, and the particle size D of the micron-sized silver powder is v50 is 6μm.
[0093] Example 16
[0094] The embodiment of the composite sheet for chip bonding and the preparation method thereof of the present invention is different from the embodiment 1 only in that the particle size D of the nano-scale silver powder is v50 The particle size D of the micron-sized silver powder is 20 nm. v50 is 10μm.
[0095] Embodiment 17
[0096] The embodiment of the composite sheet for chip bonding and the preparation method thereof described in the present invention is different from the embodiment 1 only in that the temperature of the softening annealing is 300°C.
[0097] Embodiment 18
[0098] The embodiment of the composite sheet for chip bonding and the preparation method thereof described in the present invention is different from the embodiment 1 only in that the temperature of the softening annealing is 200°C.
[0099] Embodiment 19
[0100] The embodiment of the composite sheet for chip bonding and the preparation method thereof described in the present invention is different from the embodiment 1 only in that the temperature of the softening annealing is 500°C.
[0101] Embodiment 20
[0102] The embodiment of a composite sheet for chip bonding and a preparation method thereof according to the present invention is different from the embodiment 1 only in that the silver paste used to form the silver-containing pre-sintered layer includes the following components in parts by weight per 100 parts:
[0103] 4 parts of dispersant, 2 parts of reducing agent, 5 parts of binder, 7 parts of diluent and the balance of silver powder.
[0104] Embodiment 21
[0105] The embodiment of a composite sheet for chip bonding and a preparation method thereof described in the present invention is different from Embodiment 1 only in that the time of the softening annealing is 1 hour.
[0106] Comparative Example 1
[0107] A composite sheet for chip bonding and a preparation method thereof, the difference from Example 1 is that the ratio of the thickness of the copper sheet to the silver-containing pre-sintered layer is 0.5:1;
[0108] Specifically, the thickness of the silver-containing pre-sintered layer is 0.1 mm; the thickness of the copper sheet is 0.05 mm.
[0109] Comparative Example 2
[0110] A composite sheet for chip bonding and a preparation method thereof, the difference from Example 1 is that the ratio of the thickness of the copper sheet to the silver-containing pre-sintered layer is 4:1;
[0111] Specifically, the thickness of the silver-containing pre-sintered layer is 0.1 mm; the thickness of the copper sheet is 0.4 mm.
[0112] Comparative Example 3
[0113] A composite sheet for chip bonding and a preparation method thereof, the difference from Example 1 is that the ratio of the thickness of the copper sheet to the silver-containing pre-sintered layer is 0.2:1;
[0114] Specifically, the thickness of the silver-containing pre-sintered layer is 0.1 mm; the thickness of the copper sheet is 0.02 mm.
[0115] Comparative Example 4
[0116] A composite sheet for chip bonding and a preparation method thereof, the difference from Example 1 is that the ratio of the thickness of the copper sheet to the silver-containing pre-sintered layer is 8:1;
[0117] Specifically, the thickness of the silver-containing pre-sintered layer is 0.1 mm; the thickness of the copper sheet is 0.8 mm.
[0118] Comparative Example 5
[0119] A composite sheet for chip bonding and a preparation method thereof, the difference from Example 1 is that the ratio of the thickness of the copper sheet to the silver-containing pre-sintered layer is 1.2:1;
[0120] Specifically, the thickness of the silver-containing pre-sintered layer is 0.25 mm; the thickness of the copper sheet is 0.3 mm.
[0121] Comparative Example 6
[0122] A composite sheet for chip bonding and a preparation method thereof, the difference from Example 1 is that the ratio of the thickness of the copper sheet to the silver-containing pre-sintered layer is 15:1;
[0123] Specifically, the thickness of the silver-containing pre-sintered layer is 0.02 mm; the thickness of the copper sheet is 0.3 mm.
[0124] Comparative Example 7
[0125] A composite sheet for chip bonding and a preparation method thereof, which differs from Example 1 only in that the silver powder comprises nano-scale silver powder and micron-scale silver powder, and the mass ratio of the two is 3:1.
[0126] Comparative Example 8
[0127] A composite sheet for chip bonding and a preparation method thereof, which differs from Example 1 only in that the silver powder comprises nano-scale silver powder and micron-scale silver powder, and the mass ratio of the two is 16:1.
[0128] Comparative Example 9
[0129] A composite sheet for chip bonding and a preparation method thereof, the difference from Example 1 is that the particle size D of the nano-scale silver powder is v50 Replaced with 10nm, micron-sized silver powder particle size D v50 Unchanged (still 2μm).
[0130] Comparative Example 10
[0131] A composite sheet for chip bonding and a preparation method thereof, the difference from Example 1 is that the nano-scale silver powder is replaced with a particle size D v50 The particle size of the micron-sized silver powder is 1 μm. v50 Unchanged (still 2μm).
[0132] Comparative Example 11
[0133] A composite sheet for chip bonding and a preparation method thereof, the difference from Example 1 is that the particle size D of the micron-sized silver powder is v50 Replaced with 15μm, the particle size D of nano silver powder v50 Unchanged (still 30nm).
[0134] Comparative Example 12
[0135] A composite sheet for chip bonding and a preparation method thereof, the difference from Example 1 is that the silver powder is nano-scale silver powder, and the particle size D of the nano-scale silver powder is v50 is 30nm.
[0136] Comparative Example 13
[0137] A composite sheet for chip bonding and a preparation method thereof, the difference from Example 1 is that the silver powder is micron-sized silver powder, and the particle size D of the micron-sized silver powder is v50 is 2μm.
[0138] Comparative Example 14
[0139] A composite sheet for chip bonding and a preparation method thereof, the difference from Example 1 is that the temperature of the softening annealing is 150°C.
[0140] Comparative Example 15
[0141] A composite sheet for chip bonding and a preparation method thereof, which is different from Example 1 only in that the silver paste used to form the silver-containing pre-sintered layer includes the following components in parts by weight per 100 parts:
[0142] 0.45 parts of dispersant, 0.3 parts of reducing agent, 1 part of binder, 0.8 parts of diluent and the balance of silver powder.
[0143] Comparative Example 16
[0144] A composite sheet for chip bonding and a preparation method thereof, which is different from Example 1 only in that the silver paste used to form the silver-containing pre-sintered layer includes the following components in parts by weight per 100 parts:
[0145] 5 parts of dispersant, 3 parts of reducing agent, 8 parts of binder, 9 parts of diluent and the balance of silver powder.
[0146] Comparative Example 17
[0147] A composite sheet for chip bonding and a preparation method thereof, the difference from Example 1 is that the time of the softening annealing is 0.5 h.
[0148] Effect example
[0149] In order to verify the use effect of the composite sheet of the present invention, the composite sheets obtained in each embodiment and comparative example are directly sintered on a silver-plated chip of 5*5*0.2mm in size (pressure-free sintering, 250℃, 50min), and then the shear strength of the sintered layer after sintering is tested with a push-pull tester. The greater the shear strength, the higher the interlayer bonding strength. When setting the lead bonding of the copper bonding wire, the bonding pressure is more uniform, and the protection effect of the chip will be better; then, the copper bonding wire is set at the copper sheet end of the sintered layer using a wire bonding machine. After the setting is completed, the scar area on the surface of the chip is mapped and counted (the scar usually runs through the chip, so it can be mapped from the other side of the chip that is not bonded to the sintered layer). The smaller the scar area, the better the protection effect of the product on the chip. If the scar area accounts for less than 0.1%, the scar is ignored and uniformly marked as 0%. At the same time, a blank control group is set for bare chips without composite sheet sintering layers and copper bonding wires are directly set. The test results are shown in Table 1.
[0150] Table 1
[0151]
[0152]
[0153]
[0154] As can be seen from Table 1, after use, the composite sheet of the present invention can be wire bonded without causing significant damage to the chip (in comparison, the scar area of the blank control group after setting the copper bonding wire accounted for 14.2%), and the interlayer bonding strength after sintering is high, and the shear strength of the sintered layer reaches more than 15MPa. According to Examples 1 to 6 and Comparative Examples 1 to 6, it can be seen that the use effect of the composite sheet is related to the thickness ratio of the copper sheet and the silver-containing pre-sintered layer, as well as the thickness of the silver-containing pre-sintered layer. When the ratio of the thickness of the copper sheet to the silver-containing pre-sintered layer is (1 to 3): 1 and the thickness of the silver-containing pre-sintered layer is 0.03 to 0.2 mm, the product can achieve good use effects, especially when the thickness of the silver-containing pre-sintered layer is in the range of 0.05 to 0.1 mm, the shear strength of the sintered layer after sintering is higher, which can reach more than 20MPa. If the thickness of the copper sheet or the silver-containing pre-sintered layer is improperly set, resulting in a thickness ratio exceeding the specified range, or the thickness of the silver-containing pre-sintered layer is too thin or too thick, the interlayer bonding strength of the product after sintering is not only difficult to guarantee, but may also increase the risk of chip damage. According to Example 1, Examples 7-8, Comparative Examples 7-8, and Comparative Examples 12-13, it can be seen that in the silver paste component used to form the silver-containing pre-sintered layer, the ratio of micron-level silver powder and nano-level silver powder is also critical to the performance of the product. If nano-level silver powder or micron-level silver powder is used alone to prepare the silver-containing pre-sintered layer, as shown in Comparative Examples 12-13, the sintered layer of the obtained product after sintering has almost no interlayer bonding force, the shear strength is less than 4MPa, and the protection effect on the chip is poor, and the scar area accounts for 3.4-5.8%. Only at a specific ratio can the two silver powders achieve good dispersibility and stacking compactness, thereby ensuring sufficient interlayer bonding strength. If the ratio is set too large or too small, the shear strength of the sintered layer of the product will be greatly reduced. On the other hand, when silver powders of different sizes are compounded, not any range can achieve the effect of the product of the embodiment of the present invention, especially the size setting of the nano-scale silver powder. According to Example 1, Examples 9 to 11 and Comparative Examples 9 to 10, it can be seen that the particle size of the nano-scale silver powder has a greater influence on the shear strength of the sintered layer of the product. If the particle size D v50 When the particle size is less than 20nm, the agglomeration problem is difficult to overcome, resulting in the shear strength of the final product being only 14.4MPa. v50 If the particle size is too large and reaches the micron level, even if there is still a certain gap with the particle size of micron-level silver powder, the product still cannot achieve the expected effect, and may even cause chip damage problems. It needs to be limited to a specific range. Preferably, the particle size D v50When the particle size is 30-200 nm, the use effect of the prepared product is better, and the shear strength of the sintered layer of the product after sintering can reach more than 28 MPa. Similarly, it can be seen from Example 1, Examples 12-16 and Comparative Example 11 that when the micron-sized silver powder as the skeleton is in a moderate particle size range, the prepared product has a better effect.
[0155] In addition, it can be seen from Example 1, Examples 17 to 19, Example 21 and Comparative Examples 14 and 17 that during the product preparation process, the softening annealing treatment of the copper sheet can effectively eliminate its stress and remove the oxide layer on the surface of the copper sheet, so that the bonding effect between the copper sheet and the silver-containing pre-sintered layer is better. If the temperature during the softening treatment is insufficient (as shown in Comparative Example 14), or if the softening treatment time is insufficient (as shown in Comparative Example 17), it is not only difficult to ensure the shear strength of the product sintered layer, but also will cause chip damage, and the scar area accounts for 2.3% and 2.1% respectively.
[0156] It can be seen from Example 1, Example 20 and Comparative Examples 15 to 16 that when preparing the silver-containing pre-sintered layer, attention should be paid to the ratio of the raw materials used. If the ratio is inappropriate, it is difficult to ensure the dispersibility and oxidation resistance of the silver powder and the overall density and connection strength of the obtained silver-containing pre-sintered layer, and the shear strength of the product sintered layer is low.
[0157] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the technical solution of the present invention.
Claims
1. A composite sheet for chip bonding, characterized in that: including a copper sheet and a pre-sintered layer containing silver; The thickness ratio of the copper sheet to the silver-containing pre-sintered layer is (1-3):1; The thickness of the silver-containing pre-sintered layer is 0.03 to 0.2 mm; The silver paste used to form the silver-containing pre-sintered layer includes the following components in parts by weight per 100 parts: 1-4 parts of dispersant, 0.5-2 parts of reducing agent, 2-5 parts of binder, 1.5-7 parts of diluent and the balance of silver powder; The silver powder includes nano-scale silver powder and micro-scale silver powder, and the mass ratio of the two is (5-12):1; The particle size D of the nano silver powder v50 ≥20nm; The particle size D of the micron-sized silver powder v50 ≤10μm.
2. The composite sheet for chip bonding according to claim 1, characterized in that: The thickness of the copper sheet is 0.03-0.6 mm; preferably, the thickness of the copper sheet is 0.05-0.3 mm.
3. The composite sheet for chip bonding according to claim 1, characterized in that: The thickness of the silver-containing pre-sintered layer is 0.05-0.1 mm.
4. The composite sheet for chip bonding according to claim 1, characterized in that: The particle size D of the micron-sized silver powder v50 Preferably, the particle size D of the micron-sized silver powder is v50 4~6μm.
5. The composite sheet for chip bonding according to claim 1, characterized in that: The particle size D of the nano silver powder v50 Preferably, the particle size D of the nano-scale silver powder is 20 to 500 nm. v50 It is 30~200nm.
6. The composite sheet for chip bonding according to claim 1, characterized in that: The dispersant includes at least one of vinyl pyrrolidone, polydiallyl dimethyl ammonium chloride and sodium dodecyl sulfonate; the reducing agent includes rosin acid; the binder includes α-terpineol; and the diluent includes at least one of ethylene glycol and acetone.
7. The method for preparing a composite sheet for chip bonding according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) After pre-treating the copper strip, performing a softening annealing treatment in a reducing atmosphere, and cutting to obtain a copper sheet; the temperature during the softening annealing is ≥ 200° C.; (2) The silver paste used to form the silver pre-sintered layer is prepared into a paste slurry according to the components, and then coated on a copper sheet and vacuum dried to obtain the composite sheet for chip bonding.
8. The method for preparing a composite sheet for chip bonding according to claim 7, characterized in that: The temperature during the softening annealing is 200-500°C; preferably, the temperature during the softening annealing is 300-400°C.
9. The method for preparing a composite sheet for chip bonding according to claim 7, characterized in that: The softening annealing time is ≥1h; preferably, the softening annealing time is 1-3h.
10. The method for using the composite sheet for chip bonding according to any one of claims 1 to 6, characterized in that: The following steps are involved: The silver-containing pre-sintered layer of the composite sheet is sintered directly on the chip, and then copper bonding wires are set on the copper sheet surface on the other side of the composite sheet.
Citation Information
Cited By
Composite bonding sheet and preparation method thereof, and semiconductor packaging structure and method
CN120809705A